2014
DOI: 10.5455/ijmsph.2014.050620142
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of profile of infections in diabetic and non-diabetic Patients

Abstract: Background: Diabetes mellitus is a chronic disorder and its association with an increased propensity of infection has in general, been well recognized. Clinical data on the association of diabetes mellitus with common infections are virtually lacking, not conclusive and often biased. Aims & Objective:The present study was done to determine profile of various infections with their etiological agents and antibiotic sensitivity pattern among diabetic and non-diabetic patients. Materials and Methods:A Cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…E. coli was the predominant pathogen involved with 71.86% in diabetic patients and 67.2% in non-diabetic patients followed by Klebsiella pneumoniae i.e. 15.63% in diabetic patients and 14.80% in non-diabetic patients which was in accordance to a study by Jankhwala et al [35]. Bonadia et al, 2006 found that E. coli constituted 32.5% and 31.4% followed by Enterococcus spp.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…E. coli was the predominant pathogen involved with 71.86% in diabetic patients and 67.2% in non-diabetic patients followed by Klebsiella pneumoniae i.e. 15.63% in diabetic patients and 14.80% in non-diabetic patients which was in accordance to a study by Jankhwala et al [35]. Bonadia et al, 2006 found that E. coli constituted 32.5% and 31.4% followed by Enterococcus spp.…”
Section: Discussionsupporting
confidence: 83%
“…34.5% in diabetic patients and 26.7% in non-diabetic patients was found in the study conducted in the Dhulikhel Hospital-Kathmandu University Hospital [34]. Similarly, another study found the prevalence of UTI in diabetic and non-diabetic patients to be 32% and 13% respectively [35]. Mubarak et al, 2012 reported higher prevalence of UTI among diabetic patients [36].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…There are various studies that have provided information regarding implications and management of diabetes in a dental setup (S and Choudhury, 2012;Vesterinen et al, 2012;Jankhwala, Singh and nayak, 2014). but there needs an in-depth understanding and focus towards this aspect among student practitioners as they have a comparatively lesser experience in treating such patients.…”
Section: Introductionmentioning
confidence: 99%
“…This condition brings in recurrence of infection which further results in more comorbid conditions. 4 Once an infection has developed in diabetic patients, it is difficult to treat because of impairment in microvascular circulation that limits phagocytic cell action and curtails the reach of antibiotics to the infected sites. 5 Early diagnosis of diabetic wound infection is required for the antimicrobial therapy.…”
Section: Introductionmentioning
confidence: 99%